Sistemas de controle gerencial : abordagem sob a perspectiva socioinstitucional do orçamento de uma instituição pública federal de ensino - Zambenedetti, Lidiane (2017)
The public budget seeks the satisfaction of the collective need, and therefore, the way it is planned directly affects the most diverse spheres and institutions of Brazil. This research considered the budget as a socio-institutional instrument, that is, more than a technical instrument. It was developed from theoretical foundations of the interpretative perspective, which perceive the budget as a socially constructed phenomenon, with direct implications of institutional power and social policy. In this perspective, the managerial control does not present a rational technical function directed and served by internal operations of the organization. The main objective of this research was to understand the dynamics of the budgetary process of a public institution of education in the socio-institutional perspective in relation to power relations and institutional interests. Aiming to achieve this, a qualitative research, of an explanatory nature, have been provided, through which a case study was carried out in a federal public institution of education. The data were collected through interviews, documentary analysis and observation, considering the following research question: how does the budget process of a public institution of education in the socio-institutional perspective with regard to power relations and institutional interests? Such data were analyzed by means of content analysis. The entire process was supported by the program of analysis in qualitative research, the Atlas.ti. The results show the path taken until LOA approval, as well as describe the process of internal distribution of the budget, identifying how the resources are approved after the approval of the Conif Matrix. It was observed as points of improvement in the construction of the Plan of Action the need to enumerate an order of priorities of the actions that will be taken care of, and also, to be more cautious in relation to the budgets foreseen for the exercise. As for the power relations involved in the budget process, it was found that power is, in most cases, in the community, since the entire academic community is involved in the budget planning process. Institutional interests take precedence over personal interests, leaving only a few clarified situations, such as the redistribution of resources at the end of the year. The analysis of data from extreme cases showed that in smaller camp there is greater flexibility in decision making, while the analysis of the older campuses showed that due to the fact that those responsible for budget planning are, in most cases, servers with a longer period of service in the institution, they present a certain degree of resistance, which makes the process difficult. It was also observed that three types of isomorphism act simultaneously guiding the budget process, predominating coercive isomorphism. The research launches a new look at the public budget, providing important insights from the reflections proposed here for public institutions regarding power relations and institutional interests that may involve budget planning and execution.